The king's pleasure ebook A novel of henry viii. - Weir, Alison (2023)
The New York Times bestselling author of the Six Tudor Queens series explores the private side of the legendary king Henry VIII and his dramatic and brutal reign in this extraordinary historical novel. “A delightful yarn . . . an all-around fun read about a king and a cad.”— Kirkus Reviews (starred review) Having completed her Six Tudor Queens series of novels on the wives of Henry VIII, extensively researched and written from each queen's point of view, Alison Weir now gives Henry himself a voice, telling the story of his remarkable thirty-six-year reign and his six marriages. Young Henry began his rule as a magnificent and chivalrous Renaissance prince who embodied every virtue. He had all the qualities to make a triumph of his kingship, yet we remember only the violence. Henry famously broke with the pope, founding the Church of England and launching a religious revolution that divided his kingdom. He beheaded two of his wives and cast aside two others. He died a suspicious, obese, disease-riddled tyrant, old before his time. His reign is remembered as one of dangerous intrigue and bloodshed—and yet the truth is far more complex. The King's Pleasure brings to life the idealistic monarch who expanded Parliament, founded the Royal Navy, modernized medical training, composed music and poetry, and patronized the arts. A passionate man in search of true love, he was stymied by the imperative to produce a male heir, as much a victim of circumstance as his unhappy wives. Had fate been kinder to him, the history of England would have been very different. Here is the story of the private man. To his contemporaries, he was a great king, a legend in his own lifetime. And he left an extraordinary legacy—a modern Britain.